1988
DOI: 10.1002/hep.1840080422
|View full text |Cite
|
Sign up to set email alerts
|

Renal sodium retention in cirrhosis: Tubular site and relation to hepatic dysfunction

Abstract: Renal sodium handling, assessed by the response to acute saline loading, was investigated in 14 well-compensated, nonascitic alcoholic cirrhotics and six normal controls. Urinary sodium excretion in cirrhotic patients (199 +/- 141 mumoles per min) was significantly lower than in controls (387 +/- 104 mumoles per min; p less than 0.01) at 3 hr postinfusion. In contrast to controls, renal plasma flow and glomerular filtration rate did not increase in the cirrhotics in response to acute saline loading. Proximal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…It has been shown that chronic aldosterone-receptor blockade prevents sodium retention in rats with cirrhosis induced by CCl 4 22 or common bile duct ligation. 8 However, the present study, as well as studies by others [4][5][6][7][8]23,24 shows that plasma levels of aldosterone are normal during early sodium retention in cirrhosis. This argues against hyperaldosteronism and increased collecting-duct sodium reabsorption as a major factor in early sodium retention.…”
Section: Renal Function During Early Sodium Retention In Cirrhosissupporting
confidence: 40%
“…It has been shown that chronic aldosterone-receptor blockade prevents sodium retention in rats with cirrhosis induced by CCl 4 22 or common bile duct ligation. 8 However, the present study, as well as studies by others [4][5][6][7][8]23,24 shows that plasma levels of aldosterone are normal during early sodium retention in cirrhosis. This argues against hyperaldosteronism and increased collecting-duct sodium reabsorption as a major factor in early sodium retention.…”
Section: Renal Function During Early Sodium Retention In Cirrhosissupporting
confidence: 40%
“…36 Whereas all authors agree that increased renal sodium retention occurs in cirrhosis, the opinions differ with respect to temporal relationship, mechanism, and quantitative relevance of aldosterone. 1,[37][38][39][40][41][42][43] Aldosterone receptors are transcription factors that can be activated not only by the mineralocorticosteroid aldosterone, but also by the endogenous glucocorticosteroids, cortisol and corticosterone. 6 Under normal conditions, however, only aldosterone, but not cortisol or corticosterone, has access to the MR, because a gate-keeper enzyme, the 11␤-HSD2, converts cortisol and corticosterone into glucocorticosteroids devoid of affinity for the MR, namely cortisone and dehydrocorticosterone, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…55 The elevated renal venous noradrenaline concentration in cirrhotic patients [56][57][58] suggests that augmented renal sympathetic nerve activity is a mechanism underlying the abnormal body fluid regulation in liver cirrhosis. This increase has the capacity to alter renal function by altering tubular reabsorption, renin release and renal hemodynamics, in a manner consistent with the phenomena observed in cirrhosis.…”
Section: Liver Cirrhosismentioning
confidence: 99%